Atomistic Simulations of Diamond: Implantation, Annealing, Deformation and Relaxation - Aghajamali, Alireza (Curtin University, 2020)
This thesis uses atomistic computer simulations to investigate diamond, the hardest material in the world. The computer models range from nano-sized diamonds found in ancient meteorites to diamond nanopillars that are not brittle and diamond surfaces in semiconductors. The thesis shows that computational modelling is a useful tool for studying atomistic-level processes that cannot be seen in experiment.